Quantifying rock mass bulking at a deep underground nickel mine. (January 2016) - Groccia, C.; Cai, M.; Punkkinen, A.
Highlights: Bulking factors were measured at a drift in a deep hard rock mine. Damage to the rock mass and rock support from a seismic event was documented. Various field monitoring techniques relating to bulking were experimented. Useful insight on rock mass bulking was obtained.